Some Properties of Chemical Cross-Linking Biohydrogel from Starch and Chitosan - Titi Candra Sunarti; M. Irsan Febrian; Eka Ruriani; Indah Yuliasih (International Journal of Biomaterials)
Chemical cross-linking was developed to prepare starch and chitosan-based hydrogels. First, the precursor of starch was synthesized through the reaction of carboxymethylation with sodium monochloroacetate, and then chitosan was grafted by using methacrylic acid as cross-linker. In this research, sago and cassava starches were used and mixed with chitosan, and the effect of methacrylic acid concentration was investigated to determine the grafting parameters and hydrogel characteristics. Compared to native starch and carboxymethylated starch, hydrogels from both starches have high ability to swell and high capacity to absorb water and oil. The highest grafting yield, grafting efficiency, and monomer conversion were achieved by experiment using 0.550 g of methacrylic acid per g of CMS-chitosan mixture. These hydrogels have a good potency as biodegradable absorbents for pharmaceutical and industrial application.